2006
DOI: 10.1007/s00192-006-0223-6
|View full text |Cite
|
Sign up to set email alerts
|

Hidden female urinary incontinence in urology and obstetrics and gynecology outpatient clinics in Turkey: what are the determinants of bothersome urinary incontinence and help-seeking behavior?

Abstract: The purpose of this study was to assess the prevalence of female urinary incontinence (UI) and risk factors of bothersomeness and help-seeking behavior of hidden female UI in urology and obstetrics and gynecology outpatient clinics. This multicentric and cross-sectional study was conducted as a part of the Turkish Overactive Bladder Study. Female patients (n = 5,565) who were referred with complaints other than UI and overactive bladder symptoms were surveyed using the International Consultation on Incontinenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
68
3
8

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(90 citation statements)
references
References 19 publications
11
68
3
8
Order By: Relevance
“…One Turkish study showed that frequency, severity and type of UI were independent factors for predicting bothersomeness while another Norwegian study found that increasing age, severity and UI duration were also significantly associated with consultation rate (4,17) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One Turkish study showed that frequency, severity and type of UI were independent factors for predicting bothersomeness while another Norwegian study found that increasing age, severity and UI duration were also significantly associated with consultation rate (4,17) .…”
Section: Discussionmentioning
confidence: 99%
“…The Sandvik Severity Index is a validated measurement of incontinence severity, which has been shown to correlate with the objective measurement of incontinence using a 24-hour pad test. The SSI is comprised of an index score calculated by multiplying the frequency of incontinence by the amount of urine leaked, yielding three categories of severity: slight (1-2), moderate (3)(4)(5) and severe (6-8) (8).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only 12.4%-27.7% of women in Turkey seek medical aid for UI, even though it negatively affects their life quality (5,18). In the metaanalysis study conducted by Minassian et al the researchers found that 31%-42% of women sought medical aid (27).…”
Section: Discussionmentioning
confidence: 99%
“…Among incontinence types, stress urinary incontinence (SUI) is defined as involuntary urinary leakage during effort, exercising, sneezing, and/or coughing by the International Continence Society (ICS) in their 2002 terminology report [1]. Though the numbers related to the incidence of SUI vary, generally it is observed at around 30%, with a significant number of patients between 30-60 years, and is known to be the most frequently observed incontinence type in women [2][3][4][5]. Whether urethral hypermobility or intrinsic sphincter deficiency underlies beneath the problem, urethral resistance is insufficient to oppose increased abdominal pressure, and increased pressure within the bladder, and incontinence develops.…”
Section: Introductionmentioning
confidence: 99%